A new radiological classification of the mental foramen in the edentulous mandible: clinical and surgical implications - Bruno Scognamiglio; Alfonso Acerra; Mario Caggiano; Isabella De Rubertis; Francesco Giordano (Oral and Maxillofacial Surgery, 2026)
Abstract Background The purpose of this cross-sectional study was to classify different patterns of mental nerve emergence (MNE) in edentulous mandible using cone beam computed tomography (CBCT) scans. Methods Seventy-five consecutive patients, each contributing with one hemimandible and candidates for implant surgery, were recruited at Dental Unit of University Hospital of Salerno. CBCT scans were analyzed by two calibrated examiners to assess the distance between the bone crest and the mental foramen (BC–MF), mandibular bone resorption according to the Cawood–Howell (C-H) classification and the pattern of MNE. Inter-rater agreement was evaluated using weighted Cohen’s kappa. Descriptive statistics were calculated and non-parametric tests were used to compare BC–MF distances among C-H categories and MNE classes, as well as to assess associations between categorical variables. Results Significant differences were observed among MNE-Classes with significantly higher BC–MN distance in Class I compared with Classes II and III, and in Class II compared with Class III ( p < 0.05). Moreover, a statistically significant association between the MNE class and the C-H classification ( p < 0.001) was highlighted. Conclusions Soft tissue management in the edentulous mandible requires particular attention to reduce the risk of MN injury, especially in MNE Class II and III. A statistically significant association was observed between MNE patterns and C-H classes, with higher emergence classes associated with a reduced BC-MF distance. The proposed radiological classification may support preoperative surgical planning by facilitating the identification of different patterns of MNE.